Late Termination of Pregnancy. Professional Dilemmas - Isack Kandel; Joav Merrick (The Scientific World Journal)
Abortion is an issue as long as history and hotly debated in all societies and communities. In some societies and countries it is legal, while other countries have no legal basis, and some countries have made it a crime. Today up to 90% of abortions take place in the first trimester, about 9% in the second trimester, and the rest in the third trimester.This paper deals with the issue of late termination of pregnancy, the practical medical aspects, legal issues, international aspects, and the dilemma for the professional.In early history, abortion was accepted by clergy and societies, but in recent history it is more restricted and in some countries prohibited. It does not seem that restriction leads to a lower abortion rate, but rather an active contraceptive policy, campaign, and availability to prevent pregnancies that are unwanted. In countries where abortion is restricted, the trend has been an increase in illegal abortion that leads to unsafe abortion with complications, permanent injuries, and maternal mortality.Unsafe and illegal abortion is a public health concern that governments should try to prevent and instead find ways to strengthen their commitments toward better and safer health and family planning services for women.Late termination of pregnancies is an issue of grave concern with many practical medical aspects, ethical questions, and professional dilemmas. This is especially of concern because of the viability of the fetus and should only take place in order to prevent harm to the physical and mental health of the mother or due to an anomaly or disability of the fetus.